ANALISIS USAHA IKAN OLAHAN PADA KELOMPOK PERAJIN DI KAWASAN PUSONG KOTA LHOKSEUMAWE - Muhammad Arifai; Said Herry Syafrijal; Teuku Mustaqim (Ekonis: Jurnal Ekonomi dan Bisnis, 2016)
The purpose of this study is to investigate feasibility of fish processed by craftsmen in Pusong district,of Lhokseumawe City. Based on the results, an average value of fish production received by thecraftsmen on fish processing are Rp. 50,400,000.00 permonth, while production cost of fishingprocessing has issued of Rp. 42,554,504.17. It means that they have created a profit of production,approximately Rp. 7,845,495.83 for one production process. Based on benefit and cost ratiosapproach, the value return of the acquisition cost ratio is highlighted 1.18; meaning that any addedcosts of processed fish production will increase profitability for the craftsmen of 1.84. According toother results analysis, the business of craftsmen in Pusong Baru is quite profitable to run. Craftsmenenjoyed the added value of processed fish business is also quite large at Rp 1806.50/kg. Financially,the business development of fish processing is feasible. It can be seen from NPV 0 is Rp.81,855,887, NBCR 1, 2.58, IRR = 54.99% greater than the prevailing interest rates at 15% andBEP occurs at the age of 4 years and 8 months, 22 days. However, the developing of other types offish processing is needed. It could be done by involvement of other parties in term of craftsmenempowerment to encourage of traditional home industry scale to be a modern home industry scale.Finally, the value added might be enhanced by craftsmen through products diversification.Kata kunci: Craftsmen of fish processed, feasibility of fish processed, fish production, production.